Falls in people with MS—an individual data meta-analysis from studies from Australia, Sweden, United Kingdom and the United States. (January 2015) - Nilsagård, Y; Gunn, H; Freeman, J; Hoang, P; Lord, S; Mazumder, Rajarshi; Cameron, Michelle
Background: Falls are common in people with multiple sclerosis (PwMS). Previous studies have generally included small samples and had varied methods. Objectives: The objectives of this paper are to compile fall rates across a broad range of ages and disease severity and to definitively assess the extent to which MS-associated and demographic factors influence fall rates. Methods: Individual data from studies in four countries that prospectively measured falls for three months were analyzed. We determined fall rates, prevalence of fallers (≥1 falls) and frequent fallers (≥2 falls), location and timing of falls, and fall-related demographic factors. Results: A total of 537 participants reported 1721 falls: 56% were fallers and 37% frequent fallers. Most falls occurred indoors (65%) between 6 a.m. and 6 p.m. (75%). Primary progressive MS was associated with significantly increased odds of being a faller (odds ratio (OR) 2.02; CI 1.08–3.78). Fall risk peaked at EDSS levels of 4.0 and 6.0 with significant ORs between 5.30 (2.23–12.64) and 5.10 (2.08–12.47). The fall rate was lower in women than men (relative risk (RR) 0.80; CI 0.67–0.94) and decreased with increasing age (RR 0.97 for each year, CI 0.95–0.98). Conclusion: PwMS are at high risk of falls and there are important associations between falls and MS-associated disability, gender and age.